Shoot regeneration from leaf petioles of iles-iles (Amorphophallus muelleri Blume) - MARIA IMELDA; AIDA WULANSARI; YUYU SURYASARI POERBA (Society for Indonesian Biodiversity, 2008)
Iles-iles (Amorphophallus muelleri Blume) of the Araceae is a source of carbohydrate with a high content of glucomannan which is very useful in preventing several diseases like diabetes, high blood cholesterol, high blood pressure, etc. In industry, the tuber is used as a raw material for paper pulp, textile, gum, celluloid, food and cosmetics. Generally, iles-iles is propagated by splitting tubers, bulbils or leaf cuttings, but this method can not yield high quality planting materials and sometimes may carry along many diseases. In this investigation, an in vitro method for shoot regeneration of iles-iles from petiole explants was developed. Sterilization of the explants was carried out in 0.05% HgCl2 for 20 min. after dipping in 70% ethanol and Tween 20 solution. Leaf petioles about 1 cm in length were cultured on Murashige & Skoog (MS) medium with a pH of 5.8 containing 30 g sucrose and 2.5 g Gelrite agar. The formation of adventives shoots was induced on MS medium containing 1, 2, and 4 mg/L Benzyl Amino Purine (BAP) either with or without the addition of 0.1, 0.2 and 0.5 mg/L Naphthalene Acetic Acid (NAA). Each treatment was done on 10 explants. All cultures were incubated at 26Â°C on a 16-h photoperiod with an illumination of 30 Î¼mol m-2 sec-1 provided by 40-W cool white inflorescent lights. The highest rate of shoot multiplication averaging 19 shoots per explants was achieved within 3 months on MS medium containing 2 mg/L BAP. However, the best shoot elongation was found on MS medium containing 2 mg/L BAP and 0.2 mg/L NAA.Â© 2008 Jurusan Biologi FMIPA UNS Surakarta..Key words: Amorphophalus muelleri Blume, leaf petiole culture, benzyl amino purine (BAP), naphthalene acetic acid (NAA).